Laços na diversidade: Análise da trajetória de construç\~ao do movimento social de economia solidária no Brasil - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The objective of this paper was to analyze how the process of formation of a national identity of the solidarity economy movement in Brazil was developed around a mobilizing paradigm in defense of associated work and economic relations not restricted to the mercantile sphere. In this sense, we sought to identify some of its main contextual particularities, such as: its multiplicity of subjects, its organizational strategies and its political interactions. It is a pluralistic social movement, composed of distinct identities, connected around common principles of economic organization and social reproduction. The research allowed to identify a repertoire with diversified routines of collective action, and a pattern of interaction with the public power very active, taking advantage of important contextual political opportunities, especially with respect to governments permeable to these ideas in their agendas.
Keywords: J23; J59; 330; solidarity economy; social movements; public policy; repertoires of collective action; sociology of absences and emergencies